Improving Strawberry Fruit Storability By Application Of Post Harvest Chemical Treatments (Applied Biological Research, 2012)
The present study was aimed to evaluate the effect of post-harvest  treatments on the quality and prolongation of post-harvest life of straw berryfruits cv.‘Chandler’. Strawberryfruitsweredipped either in calcium  chloride (0.5 or 1.0%) for 1 min. or 0.02% ascorbic acid for 1 min. or fumigated with glacial acetic acid for 5 min. The air-dried treated and  untreated fruits were packed in plastic punnets with ordinary cover,  LDPE cover and PVC cover and stored at 4°C. The results revealed that  physiological weight and decay loss were minimum in fruits treated with  1% CaCl2 and packed in LDPE covered punnets. Total soluble solids  increased up to 14th day and thereafter decreased; whereas, acidity  decreased in all the treatments with least decrease in fruits packed in  punnets with LDPE cover and treated with 1% CaCl2. The treatment also  showed lower acid and higher TSS. Thus 1% CaCl2 in combination with  punnets having LDPE cover was adjudged as the best treatment for  maintaining the quality and improving the shelf life of strawberry.
Keywords: Acetic acid; ascorbic acid; calcium chloride; packaging; post-harvest treatments; shelf-life; storability; strawberry